Burden of respiratory tract infections at post mortem in Zambian children. Issue 1 (December 2016) - Bates, Matthew; Shibemba, Aaron; Mudenda, Victor; Chimoga, Charles; Tembo, John; Kabwe, Mwila; Chilufya, Moses; Hoelscher, Michael; Maeurer, Markus; Sinyangwe, Sylvester; Mwaba, Peter; Kapata, Nathan; et al.
Abstract Background Autopsy studies are the gold standard for determining cause-of-death and can inform on improved diagnostic strategies and algorithms to improve patient care. We conducted a cross-sectional observational autopsy study to describe the burden of respiratory tract infections in inpatient children who died at the University Teaching Hospital in Lusaka, Zambia. Methods Gross pathology was recorded and lung tissue was analysed by histopathology and molecular diagnostics. Recruitment bias was estimated by comparing recruited and non-recruited cases. Results Of 121 children autopsied, 64 % were male, median age was 19 months (IQR, 12–45 months). HIV status was available for 97 children, of whom 34 % were HIV infected. Lung pathology was observed in 92 % of cases. Bacterial bronchopneumonia was the most common pathology (50 %) undiagnosed ante-mortem in 69 % of cases. Other pathologies included interstitial pneumonitis (17 %), tuberculosis (TB; 8 %), cytomegalovirus pneumonia (7 %) andpneumocystis Jirovecii pneumonia (5 %). Comorbidity between lung pathology and other communicable and non-communicable diseases was observed in 80 % of cases. Lung tissue from 70 % of TB cases was positive forMycobacterium tuberculosis by molecular diagnostic tests. A total of 80 % of TB cases were comorbid with malnutrition and only 10 % of TB cases were on anti-TB therapy when they died. Conclusions More proactive testing for bacterial pneumonia and TB in paediatric inpatient settings is needed.